Pembelajaran Basic English Vocabularies untuk Siswa Tingkat Sekolah Dasar, di Desa Libunio, Kecamatan So’a, Kabupaten Ngada - Ota, Maria Kristina (LPPM Universitas Flores, 2022)
English is one of the languages that have to be mastered from an early stage. Language skills that have to be mastered consist of listening, speaking, reading and writing. Vocabulary has an important role in supporting the development of language skills. Vocabulary introduced to elementary students were basic vocabularies that were easy to memorize, remember and implement in communicating. Vocabularies were presented well-equipped with pictures and students felt it easy to remember. The approach was a deductive approach equipped with game and reward. Games and rewards are very helpful in facilitating students’ active engagement during the learning process. The learning environment feels alive, not boring, and students feel happy and more relaxed